LATAR BELAKANG POLITIK PEMERTAHANAN PANGKALAN MILITER AMERIKA SERIKAT DI OKINAWA, JEPANG - NAHAR, ARIF KAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final paper explains about the background of Okinawa chosen as the location of U.S. military base and the reasons it is preserved to the present. The military base that established in Okinawa as a consequence of the implementation of the treaty of San Francisco (1951) evidently still be protected by the United States and Japan although Okinawa was returned to Japan in 1972. This final project uses the method of data retrieval / related reference, especially about the history of Okinawa, Okinawa's involvement in the Pacific War (World War II), how the United States and Japan responded to Okinawa as a U.S. military base location. In addition to written sources other references were also obtained from a few online articles, especially about the presence of U.S. military bases that still maintained its existence until today. There are two important things from the search results. First, Okinawa chosen as a U.S. military base location based on several factors, those are: (a) the strategic geographical location of Okinawa, (b) the Allies (the United States) took over the authority from Japan as a consequence of the defeat of Japan in World War II, (c) the implementation of the Treaty of San Francisco. Second, preservation of U.S. military base in Okinawa to the present due to: (a) authority that returned to Japan from the U.S on Okinawa only covers administrative, legislative, and judicial authority without relocating military base (according to the contents of Okinawa Henkan Kyootei), (b) U.S. action that does not relocate the military base also supported by Japan because they need the active military force of the United States in case their conflict with China re-occur, while Japan chose not to develop its own active military (Article 9 of the Japanese Constitution Act in 1947).